SOCIAL DIPLOMACY AND ITS CHINESE EXPERIENCE - Е.А. Керимбaев; Ц.Х. Чжaн; Н. Шaрыпкaзы (Journal of Oriental Studies, 2019)
One of the features of international relations in the 21st century is the use of soft power by developed countries to implement their long-term international strategy. This can be seen in the foreign policy of the PRC, which has recently been developing dynamically and attracting the attention of the world community. The article analyzes the theoretical foundations of PRC public diplomacy, its features and development trends, widely used by China as an instrument of soft power policy. A comprehensive consideration of the public diplomacy of the People’s Republic of China makes it possible to understand its current foreign policy principles. Key words: public diplomacy, PRC, soft power, international relations, USA, Europe, Chinese tradi- tional culture, Institute of Confucius, language, culture.